PENGEMBANGAN MEDIA KOMPOR PINTAR UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 4 - 5 TAHUN DI TK MUSLIMAT NU GINTANGAN BLIMBINGSARI BANYUWANGI - Moh. Anas Syamsudin; Endang Fitriyawati; Alex Haris Fauzi (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The learning media developed is media to improve the cognitive abilities of children aged 4-5 years at TK Muslimat NU Gintangan Blimbingsari Banyuwangi. This research aims to develop and produce products that are suitable for use to stimulate children's cognitive abilities. This type of research is the Research and Develomen (R&D) model of Borg and Gall. Of the 10 existing development steps, only 8 development steps were taken, namely 1) information collection, 2) planning, 3) initial product development, 4) trials by validation experts 5) product revisions, 6) field tests, 7) product revision II, 8) field trials. The subjects involved in this study were 1 media expert validator, 1 class teacher and 16 students. Data collection techniques used in this study are observation, interviews, questionnaires, documentation and tests. The data analysis technique used in this study is feasibility analysis using likert scale. Based on the results of validation by media experts and product trials, it can be concluded that kompor pintar media can be said to be very feasible to use. While in the effectiveness test, kompor pintar media was tested to be effective in improving children's cognitive abilities, this can be seen from the comparison of the average value obtained by children at the first meeting, which was 2.6, the second meeting increased to 2.9 and in the third meeting increased to 3.6.